G84 StreetDoctors: A public health approach to reducing youth violence. (27th April 2016) - Long, R; Jackson, S; Parkinson, A; McKenna, S; Wallace, C
Abstract : Aims: Youth violence is the third leading cause of mortality amongst young people within the European Region. The World Health Assembly has passed multiple resolutions stating violence is a public health priority and encouraging a science based public health approach. In 2013, StreetDoctors, a charity comprising medical student and junior doctor volunteers, began teaching at-risk young people, about the immediate management of pre-hospital trauma; seeking to change perspectives towards violence in order to help reduce morbidity and mortality from violent injuries. Methods: Young people, aged 12–18 years old, were identified through judicial processes. They attended two teaching modules, in centres across the United Kingdom, about haemorrhage control and managing the unconscious patient. Each session taught between 8–10 participants, with a validated, interactive module, by trained medical students and junior doctors. Qualitative and quantitative research was undertaken with immediate post-session surveys of 91 participants and staff from 16 teaching centres. The surveys involved a written Likert Scale and a group feedback session run by independent researchers. Results: End of session evaluations with young people demonstrate: 93% agreed they understood the consequences of violence (91 responses) 89% agreed they could provide medical intervention to haemorrhaging/unconscious patient (83 responses) 85% said they would be willing to act if first aid was needed (87 responses) Young people's comments include " everything in the session was useful. I learnt how to do the recovery position and chest compressions " and " if it was my enemy I'd call an ambulance. " Teaching centre surveys revealed, 100% agreed that the sessions helped young people to manage the haemorrhaging or unconscious patient, and 100% agreed that the session content made young people more aware of the medical consequences of violence (16 responses). Conclusion: Simple, replicable and interactive education of haemorrhage control and cardio-pulmonary resuscitation can change perspectives on violence and increase willingness and ability to provide medical intervention. Teaching can equip young people with the skills to save another persons life, thus helping to reduce the morbidity and mortality from youth violence and act to deter from violence.